ABO‐Compatible Retransplantation After ABO‐Incompatible Infant Heart Transplantation: Absence of Donor Specific Isohemagglutinins. Issue 12 (7th October 2014) - Kohler, S.; Engmann, R.; Birnbaum, J.; Fuchs, A.; Kaczmarek, I.; Netz, H.; Kozlik‐Feldmann, R.
<x xml:space="preserve">Abstract</x> Implementation of ABO‐incompatible (ABOi) pediatric heart transplantation has contributed to significant reduction in the mortality of infants on the waiting list, without increasing the risk of rejection. This has been attributed to the immature and therefore not fully competent immune system in this population group, which results in lower production of isohemagglutinins compared to older children and adults. Serial evaluations of isohemagglutinin titers in infants revealed cases with absence of donor specific anti‐blood group antibodies. However, it is currently unknown whether continuous exposure to donor antigens is necessary to prevent formation of donor specific isohemagglutinins (DSI) in recipients. We are reporting a case of an infant who underwent ABOi heart transplantation, with no evidence of DSI even 4 years after ABO‐compatible retransplantation. Hence, temporary exposure to donor antigens in infants may contribute to permanent absence of donor specific anti‐blood group antibodies, suggesting the possibility of induced permanent B cell tolerance.